Improving Students' Arabic Language Abilities Through Outdoor- Based Arabic Camp Program at MI Thoriqul Jannah Jambon Ponorogo - Dwi Nurcahyaningtias, Novia; Ali Sahana Anggian, Lutvi (Proceeding International Conference on Religion, Science and Education, 2025)
Language is one of the skills possessed by humans. The various languages that exist in this world are diverse and have their own characteristics. This is also the case with Arabic, which is often associated with Islam. Arabic has an important role in education. Improving Arabic vocabulary at an early age will provide a strong foundation for understanding and knowing more about the language. The purpose of this activity is the first step in introducing Arabic to students in order to provide an understanding and knowledge of Arabic culture and be able to develop Arabic language skills in the future. This activity involved 80 students of MI Thoriqul Jannah and this activity took place at MI Thoriqul Jannah. The method of this activity was carried out in 3 stages, namely the pre-implementation stage, the implementation stage and the post-implementation stage. The pre-implementation stage includes: (a) team formation (b) outline activity design (c) committee division (d) detailed activity design. The implementation stage is in the form of implementing activities based on the activity schedule. While the post-implementation stage is in the form of reflection and evaluation. The results of this activity use the evaluation of writing, reading and memorisation tests. The results show that learning Arabic through the singing method increases students' interest in learning Arabic.